All about
flooble
|
fun stuff
|
Get a free chatterbox
|
Free JavaScript
|
Avatars
perplexus
dot
info
Home
>
Just Math
>
Calculus
Exponentiate Negatively, Get Value (
Posted on 2007-12-24
)
Given that:
y
∫
(g(p))
-2
dp = g(y),
0
and:
4
∫
(g(p))
-2
dp = (12)
1/3
.
0
Find the value of g(72)
Submitted by
K Sengupta
Rating:
3.0000
(1 votes)
Solution:
(
Hide
)
g(72) = 6
EXPLANATION:
Differentiating both sides of the first relationship with respect to y, we obtain:
g’(y) = (g(y))
-2
, so that:
(g(y))
2
*g’(y) = 1
Integrating both sides w.r.t y, we obtain:
(g(y))
3
/3 = y+c
Or, (g(y))
3
= 3(y+c)……..(*)
From the first relationship, we also note that:
g(0) = 0, so that, (*) gives:
(g(0))
3
= 3c, so that:
c=0
Accordingly, (g(y))
3
= 3y, so that:
(g(72))
3
= 3*72=216
or, g(72)= 6
*** I am grateful to Chesca Ciprian, who has rightly pointed out that the second condition of the problem is superfluous.
Comments: (
You must be logged in to post comments.
)
Subject
Author
Date
re: Observation..........
K Sengupta
2008-03-06 04:35:54
re: Observation..........
Kurious
2007-12-26 08:05:19
Observation..........
Chesca Ciprian
2007-12-25 12:49:56
re(2): complete solution
Daniel
2007-12-25 10:52:58
re: complete solution
Kurious
2007-12-25 10:12:40
complete solution
Daniel
2007-12-25 02:14:37
Please log in:
Login:
Password:
Remember me:
Sign up!
|
Forgot password
Search:
Search body:
Forums (0)
Newest Problems
Random Problem
FAQ
|
About This Site
Site Statistics
New Comments (5)
Unsolved Problems
Top Rated Problems
This month's top
Most Commented On
Chatterbox:
blackjack
flooble's webmaster puzzle
Copyright © 2002 - 2025 by
Animus Pactum Consulting
. All rights reserved.
Privacy Information